Mast Cells Trigger Disturbed Bone Healing in Osteoporotic Mice - Fischer, Verena; Ragipoglu, Deniz; Diedrich, Johanna; Steppe, Lena; Dudeck, Anne; Schütze, Konrad; Kalbitz, Miriam; Gebhard, Florian; Haffner-Luntzer, Melanie; Ignatius, Anita (Journal of Bone and Mineral Research, 2021)
Mast cells are important tissue-resident sensor and effector immune cells but also play a major role in osteoporosis development. Mast cells are increased in numbers in the bone marrow of postmenopausal osteoporotic patients, and mast cell–deficient mice are protected from ovariectomy (OVX)-induced bone loss. In this study, we showed that mast cell–deficient Mcpt5-Cre R-DTA mice were protected from OVX-induced disturbed fracture healing, indicating a critical role for mast cells in the pathomechanisms of impaired bone repair under estrogen-deficient conditions. We revealed that mast cells trigger the fracture-induced inflammatory response by releasing inflammatory mediators, including interleukin-6, midkine (Mdk), and C-X-C motif chemokine ligand 10 (CXCL10), and promote neutrophil infiltration into the fracture site in OVX mice. Furthermore, mast cells were responsible for reduced osteoblast and increased osteoclast activities in OVX mice callus, as well as increased receptor activator of NF-κB ligand serum levels in OVX mice. Additional in vitro studies with human cells showed that mast cells stimulate osteoclastogenesis by releasing the osteoclastogenic mediators Mdk and CXCL10 in an estrogen-dependent manner, which was mediated via the estrogen receptor alpha on mast cells. In conclusion, mast cells negatively affect the healing of bone fractures under estrogen-deficient conditions. Hence, targeting mast cells might provide a therapeutic strategy to improve disturbed bone repair in postmenopausal osteoporosis. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2021-10-29
Keywords: FRACTURE HEALING; INFLAMMATION; MAST CELLS; OSTEOCLASTOGENESIS; OSTEOPOROSIS